2003
DOI: 10.1128/aac.47.1.130-137.2003
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Efavirenz, Nelfinavir, and Indinavir: Adult AIDS Clinical Trial Group Study 398

Abstract: The present population pharmacokinetic (PK) and pharmacodynamic (PD) study modeled the effects of covariates including drug adherence and the coadministration of protease inhibitors (PIs) on the pharmacokinetics of efavirenz (EFV) and the relationship between EFV exposure and virological failure in patients who failed initial PI treatment in Adult AIDS Clinical Trial Group (AACTG) study 398. We also report on the population PKs of the PIs nelfinavir (NFV) and indinavir (IDV). AACTG study 398 patients received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
100
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(121 citation statements)
references
References 29 publications
18
100
3
Order By: Relevance
“…This two-compartment model with first-order absorption and lag-time was similar to the model with transition compartments [28], but slightly different from the one-compartment models used for population analyses of efavirenz [8,27]. However, pharmacokinetic estimates of efavirenz obtained from the present and previous studies using different models were in good agreement.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This two-compartment model with first-order absorption and lag-time was similar to the model with transition compartments [28], but slightly different from the one-compartment models used for population analyses of efavirenz [8,27]. However, pharmacokinetic estimates of efavirenz obtained from the present and previous studies using different models were in good agreement.…”
Section: Discussionsupporting
confidence: 71%
“…The estimated average clearance of efavirenz (0.105-0.126 l/h/kg) in the present study was smaller than that previously reported in patients (0.186 l/h/kg) [26], although a recent report based on population analysis presented a value in patients given efavirenz at 600 mg/day almost identical to that found in this study [27]. For volume of distribution at steady state (V ss ), estimates ranging from 3.012 to 4.412 l/kg were consistent with literature [8,27,28]. These data along with previous observations indicate that amprenavir does not substantially alter efavirenz pharmacokinetics.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Univariate two-way ANOVA testing for significance in the change in CD4-cell count after 6 months of ART detected no discernible effect of patient ethnicity on immune response to ART. The results of this study do not confirm those of Wegner et al, 26 Pfister et al 27 and Kappelhoff et al, 28 who reported a statistically significant effect of patient ethnicity on ARV drug response. Possible explanations for these findings include a greater degree of genetic similarity between the Mixed-Ancestry and Xhosa populations, as well as the limited sample size of our cohort.…”
Section: Discussioncontrasting
confidence: 99%
“…These observations are not surprising if the hypothesis that a higher concentration of the drug correlates with a higher risk for side effects is valid. Nevirapine concentrations are consistently higher among women compared with men [28,29], but studies of efavirenz have shown varying pharmacokinetic profile results [32][33][34]. The risk for nevirapine toxicity is also related to the degree of immunocompromise.…”
Section: Influence Of Sex On Arv-associated Adverse Events In Nonpregmentioning
confidence: 99%